HUBUNGAN ANEMIA DAN KURANG ENERGI KRONIK (KEK) PADA IBU HAMIL DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI WILAYAH KERJA PUSKESMAS KANDANGAN KABUPATEN TEMANGGUNG - Yuli Astuti; Luluk Khusnul Dwihestie; Nuli Nuryanti Zulala (Jurnal Ilmu Keperawatan dan Kebidanan, 2024)
Infant mortality rate (IMR) remains a serious issue in Indonesia, and it continues to increase every year. In 2021, Puskesmas (community health center) Kandangan in Temanggung Regency had the second-highest rate of low birth weight (LBW) cases, which was 5.37%, with as many as 38 cases. In addition, there were also two neonatal deaths attributed to LBW. Anemia during pregnancy increases the risk of mothers giving birth to LBW babies due to insufficient hemoglobin, which is essential for oxygen transport and nutrient intake. Furthermore, pregnant women with chronic energy deficiency (CED) suffer from inadequate nutrient intake, which leads to reduced fetal nutrition. This research aimed to investigate the relationship between anemia, CED, and the incidence of LBW among pregnant women in the working area of Puskesmas Kandangan in Temanggung Regency. This research employed analytical observational method with retrospective approach. The population included all live-born infants in the working area of Puskesmas Kandangan in 2022, totaling 657 infants. The researchers employed a 1:1 case- control sampling method, which resulted in 102 samples—51 LBW cases and 51 normal birth weight (NBW) infants as the control group. Data analysis was done using the Chi-square (X2) formula. The findings reveal the relationship between anemia and LBW incidence which has a p-value of 0.0060.05 and an odds ratio (OR) of 0.324. Similarly, the relationship between CED and LBW incidence has a p-value of 0.0020.05 and an OR of 0.264. In conclusion, there is a significant relationship between anemia, CED, and LBW incidence among pregnant women. Mothers with anemia are three times more likely to give birth to LBW babies compared to non-anemic pregnant women. Meanwhile, mothers with CED are twice more likely to give birth to LBW babies compared to pregnant women without CED.